2020
DOI: 10.5539/jel.v9n1p164
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Functional Training on Some Biomotor Abilities and Physiological Characteristics in Elite Soccer Players

Abstract: Soccer game or a soccer match includes functional movements that require complex muscular balance including stopping, walking, jogging, sprint with dribbling, shooting and passing (Eniseler, 1994;Boyle, 2004). Functional training contribute to the different systems of the body through functional exercises performed in different parts of the body (covering the whole body, improving universal motor skills, applied in multiple motion planes) through intensive, short and constantly changing sessions. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Five studies were conducted on male athletes ( Tomljanović et al, 2011 ; Yildiz et al, 2019 ; Keiner et al, 2020 ; Elvin Chacko Philip et al, 2022 ), and three studies on female athletes ( Elbadry, 2014 ; Alonso-Fernández et al, 2017 ; Kovac et al, 2022 ). Only one study featured a mix of males and females ( Teixeira et al, 2020 ) while six did not disclose any gender information ( Sander et al, 2013 ; Abdel-Aziz Habib, 2018 ; Baron et al, 2020 ; Turna and Alp, 2020 ; Usgu et al, 2020 ; Bhardwaj and Kathayat, 2021 ). A review of the fifteen studies revealed that the respondents’ ages ranged from 9.6 to 31.0 years ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were conducted on male athletes ( Tomljanović et al, 2011 ; Yildiz et al, 2019 ; Keiner et al, 2020 ; Elvin Chacko Philip et al, 2022 ), and three studies on female athletes ( Elbadry, 2014 ; Alonso-Fernández et al, 2017 ; Kovac et al, 2022 ). Only one study featured a mix of males and females ( Teixeira et al, 2020 ) while six did not disclose any gender information ( Sander et al, 2013 ; Abdel-Aziz Habib, 2018 ; Baron et al, 2020 ; Turna and Alp, 2020 ; Usgu et al, 2020 ; Bhardwaj and Kathayat, 2021 ). A review of the fifteen studies revealed that the respondents’ ages ranged from 9.6 to 31.0 years ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intervention length: the shortest intervention length reported is 8 days (reported in one study) (Sander et al, 2013); one study reported a 5-week intervention length (Tomljanović et al, 2011); three studies reported 6week intervention lengths (Teixeira et al, 2020;Bhardwaj and Kathayat, 2021;Kovac et al, 2022); six studies reported 8week intervention lengths (Elbadry, 2014;Alonso-Fernández et al, 2017;Yildiz et al, 2019;Turna and Alp, 2020; Elvin (Baron et al, 2020); one study reported a 20-week intervention length (Usgu et al, 2020), and one study reported 10 months intervention length (the longest) (Keiner et al, 2020). Training duration: four studies did not report the duration of intervention (Tomljanović et al, 2011;Sander et al, 2013;Bhardwaj and Kathayat, 2021;Li, 2022) (Turna and Alp, 2020). Four studies did not report the frequency of training (Sander et al, 2013;Baron et al, 2020;Teixeira et al, 2020;Li, 2022).…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] Lumbar hyperextension with rotation is the common risk factor [ 28 ] for developing and aggravating spondylolysis. [ 29 ] It has been reported in some cases that extension exercise along with bracing is effective in minimizing pain and functional disability. [ 30 ] The deep extensor muscles provide compression and ultimately protection to the motion segment.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of difference between functional and conventional training may be due to advantage of multi-joint exercises (e.g., squats, push-ups) that were included in both groups, which may have overshadowed other subtle differences (Iversen et al, 2021). In elite soccer players, Turna and Alp (2020) also found no difference between functional and traditional training in biomotor abilities and physiological characteristics. Another point to note is that the outcome assessments of back extension and fatigability were both performed in a bilaterally symmetrical manner.…”
Section: Improvement In Strength and Fatigabilitymentioning
confidence: 92%